Answer:
(A) 0.0244
(B) 1 (not 1.47 as is calculated) since probability values are between 0 and 1; 0 and 1 inclusive
Step-by-step explanation:
The rare mutation only occurs in 1 generation, out of every 2048 generations. This implies that the next occurrence will fall in or within the next 2048 generations (2 generations in 4096 generations, will have the rare mutation).
(A) The probability of occurrence of this mutation at least once (at most infinity) in 50 generations of fruit flies will surely be less than, as 50 is less than 2048.
The accurate probability is gotten when 50 is divided by 2048
50÷2048 = 0.0244
(B) The probability of seeing this mutation at least once (at most infinity) in 3000 generations would have been 1.47 but for 3 reasons;
- The full question already tells that the mutation will occur once in every 2048 generations and 3000 is greater than 2048, hence there will be a sure occurrence within 3000 generations.
- Question (b) asks you to calculate the probability of seeing this mutation at least once in 3000 generations so, the probability is 1 (representing full probability).
- In probability theory or statistics, all probability values fall within 0 and 1; with 0 representing no occurrence at all and 1 representing full occurrence.
Answer:
8/81
Step-by-step explanation:
It's most efficient to simplify the quotient algebraically before inserting the values of the variables x and y.
The given expression reduces to x³ / y^4.
Substituting 2 for x and 3 for y, we get:
(2)³ 8
--------- = ---------- (Agrees with first given possible answer)
(3)^4 81
Answer:
The number is 92
Step-by-step explanation:
Let x equal the number
It is tripled
3x
Then it is tripled again
3(3x)
That equals 828
3(3x) = 828
9x =828
Divide each side by 9
9x/9 =828/9
x =92
Answer:
3x−4y=9 −3x+2y=9
Add these equations to eliminate x: −2y=18
Then solve−2y=18
for y: −2y=18 −2y −2 = 18 −2 (Divide both sides by -2)
y=−9
Now that we've found y let's plug it back in to solve for x.
Write down an original equation: 3x−4y=9
Substitute−9for y in 3x−4y=9: 3x−(4)(−9)=9
3x+36=9(Simplify both sides of the equation)
3x+36+−36=9+−36(Add -36 to both sides)
3x=−27 3x 3 = −27 3 (Divide both sides by 3) x=−9
Answer: x=−9 and y=−9
Hope This Helps!!!
Answer:
The answer to your question is: x = 7; y = 6
Step-by-step explanation:
2x+y=20 ( 1 ) Multiply by 5
6x−5y=12 ( 2 )
5 (2x+y=20) = 10x + 5y = 100
10x + 5y = 100
6x − 5y = 12 Eliminate y
16 x = 112
x = 112 / 16
x = 7
2(7) + y = 20 Substitution
14 + y = 20
y = 20 - 14
y = 6